2017
DOI: 10.1039/c6ra25872g
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose modulates insulin amyloid-like fibril formation: effect on the aggregation mechanism and fibril morphology

Abstract: Sucrose modifies the human insulin fibrillation pathways, affecting the fibril morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…We speculate that adding sucrose may influence aggregate morphology, possibly favoring more highly branched structures. 35 Fitting the remainder of the data to eqn (7) yields Df = 0.05 AE 0.02 and n 0 = 1.575 AE 0.008. This value for the monomer refractive index is consistent with expectations for proteins such as IgG.…”
Section: Polydispersity Of Porositymentioning
confidence: 99%
“…We speculate that adding sucrose may influence aggregate morphology, possibly favoring more highly branched structures. 35 Fitting the remainder of the data to eqn (7) yields Df = 0.05 AE 0.02 and n 0 = 1.575 AE 0.008. This value for the monomer refractive index is consistent with expectations for proteins such as IgG.…”
Section: Polydispersity Of Porositymentioning
confidence: 99%
“…These results are consistent with previous reports describing the influence of those disaccharides on the fibrillation inhibition of insulin as well as other proteins, that required higher concentrations to observe any beneficial effect. 69–73…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with previous reports describing the influence of those disaccharides on the fibrillation inhibition of insulin as well as other proteins, that required higher concentrations to observe any beneficial effect. [69][70][71][72][73] Both, the results of ThT assay and recovery assay for the two highest concentrations of glycopolymer additives indicated that significantly less insulin underwent fibrillation in the presence of these additives than in their absence. To further elucidate this effect, the morphologies of the amyloid fibrils formed without any additive or with pTreA 40 or pSucA 42 at the highest tested concentrations were analyzed by cryo-TEM, and representative micrographs are shown in Fig.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…Natural chemical chaperones, including myo -inositol, are typically expected to stabilize the native state of a protein, either directly by binding it or indirectly by destabilizing the unfolded state ( Beg et al, 2017 ; Clark et al, 2012 ; Dandage et al, 2015 ; Dong et al, 2019 ; Gault et al, 2018 ; Gupta et al, 2016 ; Morgan et al, 2019 ; Okiyoneda et al, 2013 ; Street et al, 2006 ). In some cases, osmolytes have been found to alter aggregate morphology ( Bashir et al, 2020 ; Marasini et al, 2017 ). Inhibitors of aggregation kinetics whose primary target is transient oligomeric states or nuclei have been more challenging to find, let alone characterize, but they are of especially high interest as possible treatments for proteinopathies ( Giorgetti et al, 2018 ; Habchi et al, 2016 ; Ignatova and Gierasch, 2006 ; Petrosyan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%